Lawyers for Nuclear Free Zone Gathering at Downtown Club - Watkins, Howard::::::::: (1988)
Ales Adamovich speaking, John Romine (arms folded), George Bulow standing; Jack Welch (burgundy coat), Leonel Alvarado (red Vest); Bill Young back center